Adverse Mechanical Ventilation and Pneumococcal Pneumonia Induce Immune and Mitochondrial Dysfunctions Mitigated by Mesenchymal Stem Cells in Rabbits. (February 2022) - Blot, Mathieu; Jacquier, Marine; Pauchard, Laure-Anne; Rebaud, Chloé; Marlin, Charline; Hamelle, Camille; Bataille, Amandine; Croisier, Delphine; Thomas, Charles; Jalil, Antoine; Mirfendereski, Hélène; Piroth, Lionel; et al.
Abstract : Background: Mechanical ventilation for pneumonia may contribute to lung injury due to factors that include mitochondrial dysfunction, and mesenchymal stem cells may attenuate injury. This study hypothesized that mechanical ventilation induces immune and mitochondrial dysfunction, with or without pneumococcal pneumonia, that could be mitigated by mesenchymal stem cells alone or combined with antibiotics. Methods: Male rabbits underwent protective mechanical ventilation (8 ml/kg tidal volume, 5 cm H2 O end-expiratory pressure) or adverse mechanical ventilation (20 ml/kg tidal-volume, zero end-expiratory pressure) or were allowed to breathe spontaneously. The same settings were then repeated during pneumococcal pneumonia. Finally, infected animals during adverse mechanical ventilation received human umbilical cord–derived mesenchymal stem cells (3 × 10 6 /kg, intravenous) and/or ceftaroline (20 mg/kg, intramuscular) or sodium chloride, 4 h after pneumococcal challenge. Twenty-four-hour survival (primary outcome), lung injury, bacterial burden, immune and mitochondrial dysfunction, and lung transcriptomes (secondary outcomes) were assessed. Results: High-pressure adverse mechanical ventilation reduced the survival of infected animals (0%; 0 of 7) compared with spontaneous breathing (100%; 7 of 7) and protective mechanical ventilation (86%; 6 of 7; both P < 0.001), with higher lung pathology scores (median [interquartile ranges], 5.5 [4.5 to 7.0] vs . 12.6 [12.0 to 14.0]; P = 0.046), interleukin-8 lung concentrations (106 [54 to 316] vs . 804 [753 to 868] pg/g of lung; P = 0.012), and alveolar mitochondrial DNA release (0.33 [0.28 to 0.36] vs . 0.98 [0.76 to 1.21] ng/μl; P < 0.001) compared with infected spontaneously breathing animals. Survival (0%; 0 of 7; control group) was improved by mesenchymal stem cells (57%; 4 of 7; P = 0.001) or ceftaroline alone (57%; 4 of 7; P < 0.001) and improved even more with a combination treatment (86%; 6 of 7; P < 0.001). Mesenchymal stem cells reduced lung pathology score (8.5 [7.0 to 10.5] vs . 12.6 [12.0 to 14.0]; P = 0.043) and alveolar mitochondrial DNA release (0.39 (0.34 to 0.65) vs . 0.98 (0.76 to 1.21) ng/μl; P = 0.025). Mesenchymal stem cells combined with ceftaroline reduced interleukin-8 lung concentrations (665 [595 to 795] vs . 804 [753 to 868] pg/g of lung; P = 0.007) compared to ceftaroline alone. Conclusions: In this preclinical study, mesenchymal stem cells improved the outcome of rabbits with pneumonia and high-pressure mechanical ventilation by correcting immune and mitochondrial dysfunction and when combined with the antibiotic ceftaroline was synergistic in mitigating lung inflammation. Abstract : In a preclinical study, mesenchymal stem cell administration improved the outcome of rabbits with pneumonia and high-pressure mechanical ventilation by correcting immune and mitochondrial dysfunction. When combined with specific antibiotic therapy, the combination was synergistic in mitigating lung inflammation.Supplemental Digital Content is available in the text.